1995
DOI: 10.1007/bf02148848
|View full text |Cite
|
Sign up to set email alerts
|

Acute pouchitis and deficiencies of fuel

Abstract: Deficiency of SCFA is implicated in acute pouchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Bacterial overgrowth disproportionately favors anaerobes, leading to bacterial dysbiosis, another purported cause of pouchitis [37]. Overgrowth or dysbiosis can lead to deficiencies in essential nutrients, such as butyrate [38] and glutamine [39], both purportedly required for optimal enterocyte function. In addition, the overgrowth of bacteria, especially anaerobes, can catalyze the excess production of secondary bile acids [40] not typically present in high concentrations in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial overgrowth disproportionately favors anaerobes, leading to bacterial dysbiosis, another purported cause of pouchitis [37]. Overgrowth or dysbiosis can lead to deficiencies in essential nutrients, such as butyrate [38] and glutamine [39], both purportedly required for optimal enterocyte function. In addition, the overgrowth of bacteria, especially anaerobes, can catalyze the excess production of secondary bile acids [40] not typically present in high concentrations in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the ileal J pouch becomes significantly inflamed after 30 days and DSS can be successfully used to reproducibly exacerbate ileal pouch inflammation and produce accompanying diarrhea, mucosal ulcerations, and rectal bleeding, similar to clinical pouchitis. It is well known that fecal stasis has been directly implicated in bacterial overgrowth [29] and bacterial dysbiosis [30]. In the Shebani study both aerobes and anaerobes overgrow the ileal pouch by 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…In the Shebani study both aerobes and anaerobes overgrow the ileal pouch by 30 days. This atypical bacterial environment in the ileal J pouch can predispose ileal enterocytes to a number of pathophysiological conditions purportedly associated with pouchitis, including SCFA deficiencies [30]. Such nutrient alterations have been shown to compromise mucosal homeostasis, epithelial integrity, and barrier function [31].…”
Section: Discussionmentioning
confidence: 99%
“…Possible causes are fecal stasis resulting in bacterial overgrowth and infection 12 , microbial imbalance 13 , production of volatile fatty acids 14,15 , ischemia 14 , oxygen free radical injury 16 , nitric oxide 17 , deprivation of short chain fatty acids 18,19 , and extracolonic manifestation of ulcerative colitis. Penna et al 20 reported a strong correlation between primary sclerosing cholangitis and pouchitis, suggesting a common link in their pathogenesis.…”
Section: Discussionmentioning
confidence: 99%